Efficient CRISPR/Cas9 Genome Editing of Phytoene desaturase in Cassava - Odipio, John; Alicai, Titus; Ingelbrecht, Ivan; Nusinow, Dmitri A.; Bart, Rebecca; Taylor, Nigel J. (Frontiers in Plant Science, 2017)
CRISPR/Cas9 has become a powerful genome-editing tool for introducing genetic changes into crop species. In order to develop capacity for CRISPR/Cas9 technology in the tropical staple cassava (Manihot esculenta), the Phytoene desaturase (MePDS) gene was targeted in two cultivars using constructs carrying gRNAs targeting two sequences within MePDS exon 13. After Agrobacterium-mediated delivery of CRISPR/Cas9 reagents into cassava cells, both constructs induced visible albino phenotypes within cotyledon-stage somatic embryos regenerating on selection medium and the plants regenerated therefrom. A total of 58 (cv. 60444) and 25 (cv. TME 204) plant lines were recovered, of which 38 plant lines (19 from each cultivar) were analysed for mutagenesis. The frequency of plant lines showing albino phenotype was high, ranging from 90% to 100% in cv. TME 204. Observed albino phenotypes were comprised of full albinos devoid of green tissue and chimeras containing a mixture of white and green tissues. Sequence analysis revealed that 38/38 (100%) of the plant lines examined carried mutations at the targeted MePDS site, with insertions, deletions and substitutions recorded. One putatively mono-allelic homozygous line (1/19) was found from cv. 60444, while one (1/19) and four (4/19) putatively bi-allelic homozygous lines were found in 60444 and TME204, respectively. The remaining plant lines, comprised mostly of the chimeras, were found to be putatively heterozygous. We observed minor (1 bp) nucleotide substitutions and or deletions upstream of the 5’ and or downstream of the 3’ targeted MePDS region. The data reported demonstrates that CRISPR/Cas9-mediated genome editing of cassava is highly efficient and relatively simple, generating multi-allelic mutations in both cultivars studied. Modification of MePDS described here generates visually detectable mutated events in a relatively short time frame of 6-8 weeks, and does not require sequencing to confirm editing at the target. It therefore provides a valuable platform to facilitate rapid assessment and optimization of CRISPR/Cas9 and other genome editing technologies in cassava.